The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1210/en.2011-2171
|View full text |Cite
|
Sign up to set email alerts
|

Impairments to the GH-IGF-I Axis in hSOD1G93A Mice Give Insight into Possible Mechanisms of GH Dysregulation in Patients with Amyotrophic Lateral Sclerosis

Abstract: GH deficiency has been found in subjects with amyotrophic lateral sclerosis (ALS). Disrupted endocrine function could contribute to the progressive muscle loss and hypermetabolism seen in ALS. It is not possible to study all the elements of the GH-IGF-I axis in ALS patients. Consequently, it remains unclear whether dysfunctional GH secretion contributes to disease pathogenesis and why GH and IGF-I directed treatment strategies are ineffective in human ALS. The hSOD1(G93A) transgenic mouse model is useful for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 70 publications
4
27
0
1
Order By: Relevance
“…At 25 weeks of age, the end-stage of disease [67,74], and relative to untreated wild-type mice, hSOD1 G93A mice showed reduced gene expression for succinate dehydrogenase ( Sdha , 70%), Gpt2 (84%) and the β subunit of propionyl carboxylase ( Pccb , 64%) (all p<0.05 in post test, Figs 4–6). Triheptanoin prevented the reduction in the expression of these genes, indicating that it can preserve muscle energy metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…At 25 weeks of age, the end-stage of disease [67,74], and relative to untreated wild-type mice, hSOD1 G93A mice showed reduced gene expression for succinate dehydrogenase ( Sdha , 70%), Gpt2 (84%) and the β subunit of propionyl carboxylase ( Pccb , 64%) (all p<0.05 in post test, Figs 4–6). Triheptanoin prevented the reduction in the expression of these genes, indicating that it can preserve muscle energy metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Indirectly, increased circulating IGF-1 could be a fingerprint of higher GH-IGF1 axis activity, and GH is able to modulate oligodendroglial cell survival and myelination in the CNS 27 . Interestingly growth hormone secretion was dysregulated in both patients and mouse models of ALS 28 . Results from experimental studies indicate a circadian control of IGF-I production 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that tissue iron accumulation is associated with several morbidities; however, it is still not clear if the phenomenon is a cause or effect of the disease process . There is evidence that insulin and insulin‐like growth factor 1 signalling is impaired in the skeletal muscle of transgenic animals, as well as in the animal model of ALS, and also in patients presenting with ALS or cancer patients with cachexia . In other experimental models, it has been demonstrated that excess tissue iron accumulation is associated with impaired insulin signalling .…”
Section: Introductionmentioning
confidence: 99%
“…7 There is evidence that insulin and insulin-like growth factor 1 signalling is impaired in the skeletal muscle of transgenic animals, as well as in the animal model of ALS, and also in patients presenting with ALS or cancer patients with cachexia. 8,9 In other experimental models, it has been demonstrated that excess tissue iron accumulation is associated with impaired insulin signalling. 10 Phlebotomy is known to decrease body iron stores and improve insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%